Recursos digitales en el aprendizaje basado en problemas en estudiantes de bachillerato en ciencias, Unidad Educativa Eugenio Espejo - Morla Barco, Evelyn Liliana (2023)
This research is based on the prevailing need to understand the educational approach in a digital environment of constant transformation. Its main objective lies in determining the influence of digital resources on Problem-Based Learning of Baccalaureate in Science students, from the Eugenio Espejo Educational Unit. In addition to this central objective, specific objectives are highlighted, which focus on investigating current challenges, identifying available digital resources and diagnosing their effectiveness in the educational process. Regarding the methodology, two types of research were used, specifically, exploratory and descriptive. As the main technique, a survey was used that led to a questionnaire that was composed of questions related to the topic. This survey was applied to both students and teachers, and the results obtained reflected that both parties agree that the incorporation of digital resources improves the understanding of educational content. Regarding the conclusions, it reflects that these digital resources are essential and viable in the current educational environment. The research lays the foundation to understand how technology can enhance problem-based learning in the constantly evolving digital context, however, favorably there is a growing awareness that PBL can better prepare students to face situations in the world of work, generating thus a positive impact on society.